Uji Toksisitas Ekstrak Etanol Batang Petai Cina (Leucaena leucochepala) Terhadap Cacing Gelang Ayam (Ascaridia galli) - Febriana Rahmadani; Siwi Hastuti (STIKES MUHAMMADIYAH KLATEN, 2020)
Leucaena stem ( Leucaena leucochapala ) was a plant that has been widely known and used as a medicinal treatment. This plant contains tanins, saponins and flavonoids. Was to know the toxicity for ethanol extract of (Leucaena leucochepala) towards (Ascaridia galli) with in vitro method. In this study there were 10 serial dilutions of the dose, the highest dose was 5000 µg/ml of ethanol extract of Leucaena leucochepala plus 0,3 ml of DMSO and dilution with NaCl 0,9. Used 150 tail worm’s added 15 tails to control. The result is observed by 24 hours. Data have been obtained by calculating amount of died worm’s 24 hours after treatment. Through the data, LC50 value was analyzed by probit analysis. This experimental’s result was a significant correlation betweenconcentrations of petai cina extract and worm’s death. The results of the probit analysis showed LC50 price of ethanol extract of Leucaena leucochepala was 5751,451 µg/ml. It means that the petai cina stem has toxic potential because it LC50 is < 1000 µg/ml. Extract of ethanol stems petai cina producted showed that the test toxicity acutely one plants with the in vitro declared toxic. And the price LC50 that established is 5751,451 µg/ml declared toxic.